2010
DOI: 10.1021/jz100233w
|View full text |Cite
|
Sign up to set email alerts
|

Cs-Modified WO3 Photocatalyst Showing Efficient Solar Energy Conversion for O2 Production and Fe (III) Ion Reduction under Visible Light

Abstract: Cs-modification effects of WO3 on photocatalytic O2 evolution and Fe (III) ion reduction over WO3 under visible light irradiation were investigated. WO3 having cation-exchange ability at the surface was successfully prepared by hydrothermal and impregnation methods using cesium aqueous solutions. The photocatalytic activity of Cs-modified WO3 was partially improved by the ion-exchange of Cs+ for H+ and Fe2+, and more than 10 times higher than that of WO3 without any treatment. The optimized WO3 showed 48 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 21 publications
2
84
1
Order By: Relevance
“…Figure 6 shows XRD patterns of the film and the calcined powder of WO 3 ·H 2 O precipitates. Both patterns could be assigned to monoclinic WO 3 . The peak intensity of 002 diffraction for the film was found to be much higher than that for the particles.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 6 shows XRD patterns of the film and the calcined powder of WO 3 ·H 2 O precipitates. Both patterns could be assigned to monoclinic WO 3 . The peak intensity of 002 diffraction for the film was found to be much higher than that for the particles.…”
Section: Resultsmentioning
confidence: 92%
“…A simple heat-treatment of tungstite (WO 3 .H 2 O) allows for the phase transformation to tungsten oxide (WO 3 ), an important class of n-type semiconductors with a tunable band gap of 2.5-2.8 eV [16]. Moreover, its high chemical stability, low production costs and non-toxicity have recently generated significant interests for a wide variety of applications in microelectronics and optoelectronics [17][18], super-hydrophilic thin films [15], dye-sensitized solar cells [19], colloidal quantum dot LEDs [20], photocatalysis [21] and photoelectrocatalysis [22], water splitting photocatalyst as main catalyst [23][24][25][26][27][28][29][30][31][32][33][34]. Environmental applications can also benefit from WO 3 as a visible light photocatalyst to generate OH radicals for bacteria destruction [35] and photocatalytic reduction of CO 2 into hydrocarbon fuels [36].…”
Section: Introductionmentioning
confidence: 99%
“…Development of a photoelectrode material with visible light response has been sought for efficient utilization of solar energy. It has been reported that Fe 2 O 3 (9-11), WO 3 (12)(13)(14), BiVO 4 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and SrTiO 3 ∶Rh (25) of metal oxide electrodes respond to visible light. Recently, some (oxy) nitride materials such as TaON (26,27), Ta 3 N 5 (27,28), SrNbO 2 N (29), and Ta 0.9 Co 0.1 N x (30) have also been found to be visible light responsive photoelectrodes for water splitting.…”
mentioning
confidence: 99%